2021
DOI: 10.1590/1980-549720210007.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of avoidable fetal mortality and social deprivation

Abstract: Objective: To develop a social need index for stratification of municipalities and identification of priority areas for reducing fetal mortality. Methods: ecological study, carried out in the state of Pernambuco, between 2010 and 2017. The technique of factor analysis by main components was used for the elaboration of the social need index. In the spatial analysis, the local empirical Bayesian estimator was applied and Moran's spatial autocorrelation was verified. Results: The social deprivation index select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This rate is an indicator that reflects the access and quality of healthcare services and signals the existence of deficiencies in the healthcare provided 11 . This gradient is consistent with the result obtained in a capital in Northeastern Brazil, which also identified an increase in the rates of avoidable fetal mortality in regions marked by the presence of greater social deprivation 28 .…”
Section: Discussionsupporting
confidence: 91%
“…This rate is an indicator that reflects the access and quality of healthcare services and signals the existence of deficiencies in the healthcare provided 11 . This gradient is consistent with the result obtained in a capital in Northeastern Brazil, which also identified an increase in the rates of avoidable fetal mortality in regions marked by the presence of greater social deprivation 28 .…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the associations identified in the analyzed area make it possible to assess the services and the socioeconomic development of the region 18,40 . The results reinforce what has already been described in other studies [42][43][44] , suggesting the need for intervention and implementation of health programs and public policies to maintain care for mothers and newborns in municipalities with spatial dependence 46 , with the objective of reversing the negative effects of LBW 16 and mitigating the risk of infant death.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, given the efforts of many countries to reduce mortality, in recent years several studies have analyzed cases of LBW and their association with mortality [13][14][15][16][17] . Besides, thanks to geographic information systems (GIS) and spatial distribution studies, it is possible to analyze and apply geographic analytical methods to spatial data for mapping and identifying clusters and risk areas in health problems [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the social dynamics of health problems differ spatially (Yourkavitch et al, 2018). A study carried out in different municipalities in the state of Pernambuco, Brazil, showed that variables representing social need are related to foetal mortality (Canuto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of clusters at the municipality level in a large part of Pernambuco State found in this study reflects health inequalities. There is a need to identify the barriers access to primary healthcare services and the quality provided there (Canuto et al, 2021). In economically disadvantaged places, spatial differences regarding early neonatal mortality rates are linked to health inequalities and, consequently, also to uneven distribution of, and differentiated access to, healthcare services (Boutayeb et al, 2020).…”
Section: Discussionmentioning
confidence: 99%